Nusantara's Northern Neighbors: Brunei, Sabah, Sarawak, and the Prospects of a Pan-Borneo Railway in ASEAN - Lee, Brice Tseen Fu; Sims, Juan Pablo; Ouyang, Hanzhen; Komšić, Filip; Bettani, Salman Ali (Universitas Negeri Semarang, 2024)
Borneo, the world's third-largest island, presents a unique intersection of diverse ecosystems and indigenous cultures set within the complexities of Southeast Asia's socio-economic and geopolitical fabric. This research delves into the developmental trajectories of Sabah, Sarawak, and Brunei, emphasizing their historical resource endowments and contemporary challenges. Positioned against the backdrop of Indonesia's Nusantara initiative, which seeks to galvanize Kalimantan's growth, this study articulates strategic pathways for the northern territories. Drawing from comprehensive evaluations, it bridges the existing literature gap by integrating analyses of critical resources, exploring the viability of the Pan-Borneo Railway, and examining its potential impacts. Moreover, it provides comparative insights with other regional transport projects and underscores Borneo's potential transformation into a pivotal trade nexus. The study culminates by highlighting how fortifying Northern Borneo's capabilities could reciprocally amplify Kalimantan's regional prominence. The research underscores the need for collaborative imperatives and strategic integration.